2016
DOI: 10.1007/s12105-016-0760-3
|View full text |Cite
|
Sign up to set email alerts
|

S-100 Negative Granular Cell Tumor (So-called Primitive Polypoid Non-neural Granular Cell Tumor) of the Oral Cavity

Abstract: Four cases of cutaneous S-100 negative granular cell tumor were described in 1991. Until now, only 3 cases of oral involvement have been documented in English literature. Two additional cases of oral S-100 negative granular cell tumor are described. Immunohistochemical markers were applied to exclude other lesions that may show the presence of granular cells. The clinical findings were correlated with the histopathological and immunohistochemical features to arrive at the appropriate diagnosis. S-100 negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 25 publications
1
15
0
6
Order By: Relevance
“…Regrettably, in the study, the authors did not consider the pre-existing literature cases of the glabrous mucosal lesions; particularly, 5 NNGCT cases of the oral cavity have been previously reported. [2][3][4][5] Although the fact that NNGCTs can arise in the glabrous mucosa can reject the conclusion by Fernandez-Flores et al, in my review of the literature, some of these oral cases might have been incorrectly diagnosed. At least 1 of the 5 oral cases could be a histiocytic lesion, as histiocytoid cytomorphology was observed and immunohistochemical analysis was insufficient.…”
Section: To the Editormentioning
confidence: 79%
“…Regrettably, in the study, the authors did not consider the pre-existing literature cases of the glabrous mucosal lesions; particularly, 5 NNGCT cases of the oral cavity have been previously reported. [2][3][4][5] Although the fact that NNGCTs can arise in the glabrous mucosa can reject the conclusion by Fernandez-Flores et al, in my review of the literature, some of these oral cases might have been incorrectly diagnosed. At least 1 of the 5 oral cases could be a histiocytic lesion, as histiocytoid cytomorphology was observed and immunohistochemical analysis was insufficient.…”
Section: To the Editormentioning
confidence: 79%
“…3 However, other locations have been reported, the oral cavity being the most common extracutaneous site. 4 T A B L E 2 Immunohistochemical studies performed Epithelioid cell histiocytoma (ECH) may also show granular cell changes, and its resemblance to the exophytic variant of NNGCT has been reported previously. 12,13 It has been suggested that ECH with granular cell change and NNGCT are one and the same neoplasm, 14 particularly in light of a recent description of ALK overexpression in both tumors.…”
Section: Discussionmentioning
confidence: 92%
“…NNGCT usually presents as a polypoid or plaque‐like lesion, most commonly on the trunk 3 . However, other locations have been reported, the oral cavity being the most common extracutaneous site 4 …”
Section: Discussionmentioning
confidence: 99%
“…During the selection process of the systematic review, five publications reporting 6 S100 (−) cases were excluded (Basile & Woo, ; Lerman & Freedman, ; Mejía, Rubiano, Osorio, & González, ; Rawal & Dodson, ; Solomon & Velez, ). These lesions occurred more commonly in men, and the clinical image was different to normal oral GCT, with one lesion developing in the alveolar ridge over a tooth extraction site (Lerman & Freedman, ).…”
Section: Discussionmentioning
confidence: 99%